Moderating role of product type in the relationship between e-retailer service attributes and customer satisfaction. (2017) - You, Yanfen; Bhatnagar, Amit; Ghose, Sanjoy
This paper examines how product type (i.e., utilitarian vs. hedonic) moderates the relationship between e-retailer service attributes (i.e., customer support and product met expectations ) and customer satisfaction. Using hierarchical linear regression analysis, this paper finds that customer support exerts a stronger impact on customer overall satisfaction for utilitarian goods than for hedonic goods. In contrast, product met expectations exerts a greater impact on customer overall satisfaction for hedonic goods than for utilitarian goods. Managerially, it is of strategic importance for e-retailers to account for their product types when allocating resources to service attributes. Theoretically, this is the first study to explore the moderating role of product type (i.e., utilitarian vs. hedonic) in the relationships between e-retailer service attributes and customer overall satisfaction.